Initiating highly efficient (Bi, Ce)2(O, S)3−x oxysulfide catalysts with rich oxygen vacancies for hydrogen evolution via adjusting valence band configuration. Issue 8 (1st February 2023) - Chen, Xiaoyun; Wu, Qinhan; Kuo, Dong-Hau; Abdeta, Adugna Boke; Zhang, Hanya; Li, Ping; Huang, Ting; Zelekew, Osman Ahmed; Lin, Jinguo
Abstract : Converting Bi2 S3 into an efficient PHER catalyst by defect engineering to form solid solutions with the incorporation of Ce and O into Bi2 S3 for bimetal–chalcogen (Bi, Ce)2 (O, S)3− x catalysts. Abstract : The role of oxygen vacancies (VO ) in semiconductors' photocatalytic hydrogen evolution reaction (PHER) activities is challenging. In this study, BiCeOS with different VO abundances and n(Ce 3+ /Ce 4+ ) amounts prepared by adjusting the hydrazine amount was evaluated. The theoretical and experimental results indicated that VO converts tetravalent cerium into trivalent cerium to maintain electrical neutrality by creating an electron donor level in the band gap of BiCeOS. Thus, BiCeOS with rich VO and higher n (Ce 3+ /Ce 4+ ) amounts exhibits higher visible light–excited photocurrent and easier photoinduced charge separation than those of BiCeOS with poor VO and lower n (Ce 3+ /Ce 4+ ) amounts. DFT calculations indicate that BiCeOS with rich VO strongly interacts with water at a high adsorption energy of −0.968 eV to form a distorted water molecule. Therefore, the introduction of VO on the surfaces with subsequently partial Ce 4+ -to-Ce 3+ conversion remarkably yields BiCeOS catalysts with excellent visible light PHER activities.